Reposisi Kedudukan Saudara Dalam Hukum Waris Islam - Juandi, Juandi (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2017)
Islamic inheritance law makes three categories of siblings with different parts. This difference shows that the position of siblings, siblings of one father and siblings of one mother is not the same. This is understood from the explanation of the different inheritance of the brother in the Qur'an, namely verse 12 and verse 176 surah an-Nisa '. This reading leaves a problem because in reality there is no significant importance in the distinction except the attempt to reconcile the two verses. By using a systematic reading of the theme of kalalah followed by the theory of the primary and secondary heirs, it is found that the difference in the brother's part as the heir is more to the difference of his position as the primary or secondary heir, not the difference as a sibling, siblings of one father and siblings of one mother. Therefore the repositioning of sibling position in Islamic law of inheritance should be applied.